2013
DOI: 10.2807/1560-7917.es2013.18.50.20661
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous case of dengue in France, October 2013

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 61 publications
0
91
0
5
Order By: Relevance
“…No severe clinical variants or deaths were reported [102,104]. In addition, one autochthonous case was reported in southern France in October 2013 [105]. While Aedes aegypti is re-emerging in Europe, Aedes albopictus is emerging [106,107] and an overall increase in Dengue risk is predicted, with the greatest increase expected in coastal areas of southern Europe [103]; see Table 7.…”
Section: Climate-sensitive Infectious Diseasesmentioning
confidence: 99%
“…No severe clinical variants or deaths were reported [102,104]. In addition, one autochthonous case was reported in southern France in October 2013 [105]. While Aedes aegypti is re-emerging in Europe, Aedes albopictus is emerging [106,107] and an overall increase in Dengue risk is predicted, with the greatest increase expected in coastal areas of southern Europe [103]; see Table 7.…”
Section: Climate-sensitive Infectious Diseasesmentioning
confidence: 99%
“…Ae. albopictus was first detected in France in 2004 (101); it is now well established in the southern part of the country, where it was responsible for local transmission of dengue (102,218) and chikungunya (219). Ae.…”
Section: Imported Cases Of Zika Fever and Risk Of Dissemination In Armentioning
confidence: 99%
“…Transmission in this area seems to be only possible during the warm seasons. The vector is spreading to new areas, as reported in France [67,68], where a recent study confirmed the high efficiency of temperate Ae. albopictus to transmit CHIKV [69•].…”
Section: Epidemiology Of Chikv By Continentmentioning
confidence: 52%